El ruido, un contaminante del medio ambiente y sus efectos sobre la salud humana - Restrepo Díaz, María Cristina (Revista Estomatología, 2002)
The reduction and detriment of the hearing sense is a consequense of diverse causes. One of these the prolonged exposition to noise. It affects hearing slowly and has an irreversible character. The noise decreases communication effectiveness, so it has physical consequences, psychological alterations and behavior changes. Noise is an environmental polluter that influence quality life. It is risk factor that makes necessary adapting preventive measures and education at every work.